Regularly Drinking Alcohol Before Sexual Activity in a Nationally Representative Sample: Prevalence, Sociodemographics, and Associations With Psychiatric and Substance Use Disorders - Eaton, Nicholas R. (Am J Public Health, 2015)
Objectives. We addressed regular drinking before sex and its associated risk factors. Methods. From the wave 2 National Epidemiologic Survey on Alcohol and Related Conditions, a nationally representative adult US sample (fielded 2004–2005), we determined the 12-month prevalence of regularly drinking alcohol before sexual activity. Among 17 491 sexually active drinkers, we determined the sociodemographic, psychiatric, and substance use correlates of regularly drinking before sex. Results. Regular presex drinking’s 12-month prevalence was 1.8%. Significant bivariate sociodemographic correlates were age, gender, race/ethnicity, education, family income, marital status, and employment status. Generalized anxiety disorder and alcohol dependence were associated with significantly increased odds of being a regular presex drinker after controlling for covariates. Conclusions. We estimate that 4.3 million American adults are regular presex drinkers. Future research should examine this public health issue at the population level, with particular focus on pathways that link it to psychopathology.